1991
DOI: 10.1002/pd.1970110403
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of recurrent Larsen syndrome: Further definition of a lethal variant

Abstract: Larsen syndrome is characterized by multiple congenital joint dislocations and flattened facies. Some cases have been familial, with both autosomal dominant and recessive patterns of inheritance. Reports of a form of Larsen syndrome, lethal in the neonatal period, are reviewed. We present a family in which recurrence of the syndrome was diagnosed prenatally, but a lethal outcome again resulted despite preparation for anticipated perinatal complications. Because of the wide clinical variation and the lack of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 14 publications
1
44
0
1
Order By: Relevance
“…These data support Mostello et al, 31 who stated that no clinical, radiographic or histological marker separates several reports compatible with a recessively inherited entity 13 26 31 from those that describe the dominantly transmitted phenotype, now known to be caused by mutations in FLNB. These putative recessive entities may represent further instances of parental germline mosaicism for a heterozygotic FLNB mutation.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These data support Mostello et al, 31 who stated that no clinical, radiographic or histological marker separates several reports compatible with a recessively inherited entity 13 26 31 from those that describe the dominantly transmitted phenotype, now known to be caused by mutations in FLNB. These putative recessive entities may represent further instances of parental germline mosaicism for a heterozygotic FLNB mutation.…”
Section: Discussionsupporting
confidence: 85%
“…26 36 However, clear criteria that definitively delineate recessively inherited forms of Larsen syndrome from the dominantly inherited entity have not been established. 13 31 Laville et al 36 and Bonaventure et al 37 described several large families, from La RĂ©union Island, which segregated a phenotype resembling Larsen syndrome, but with severe short stature, advanced skeletal maturation, diaphyseal bowing and lethality in childhood. Recurrence of the phenotype to unaffected parents in an isolated population firmly implicates an autosomal recessive mode of inheritance.…”
mentioning
confidence: 99%
“…3 Furthermore, it became apparent that not all individuals with Larsen syndrome harbor FLNB mutations and that the long-debated autosomal-recessive forms of the disease do exist. [4][5][6] The first was characterized in 2008 by Hermanns et al, who identified biallelic variants in CHST3 (MIM: 603799) as a major cause of an autosomal-recessive form that differs from FLNB-related forms by its generalized joint laxity and lack of the typical facial appearance. 7 Subsequently, a founder variant in B4GALT7…”
Section: (Mim: 150250) the Inheritance Ofmentioning
confidence: 99%
“…However, an emergency procedure at 37 weeks gestation became necessary because of persistent fetal bradycardia. The infant died 8 days later due to failure of the respiratory system despite continuous intensive care support [4]. In the second case report of prenatal diagnosis and obstetric management of Larsen's syndrome, the physicians were alert of the disorder in a pregnant woman with an established diagnosis of Larsen's syndrome at the age of 11 years and with a positive family history for the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 1972, 33 cases could be traced in the literature [3]. Of the at least 15 further reports on Larsen's syndrome in the last decade with a total of 41 cases [1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17], we could identify only two reports with a prenatally suspected diagnosis of Larsen's syndrome [4,10]. The condition may be inherited in either an autosomal dominant or autosomal recessive form [18], which cannot be differentiated by clinical findings.…”
Section: Introductionmentioning
confidence: 99%